Assessment of Individual and Multiple Nanoparticles on Electrical Insulation of Power Transformers Nanofluids. Issue 4 (16th March 2019) - Thabet, A.; Allam, M.; Shaaban, S. A.
Abstract: This paper investigates on the impacts of individual and multi-nanoparticles on effective conductivity (static and electrophoretic) of transformer oils. Also, it has been investigated on the main effective factors of effective electrical conductivity for transformer oil nanofluids like; concentration of nanoparticles, applied electric field, and thermal conditions. A simulation study has been performed for using individual and multiple nanoparticles (SiO2, ZnO, TiO2, and Graphite) based on static and electrophoretic conductivities. An experimental work has been carried out for verifying the importance of using multiple nanoparticles for controlling in conductivity of power transformers nanofluids. Finally, a comparative study has been done for specifying the optimal nanoparticles for controlling on conductivity of transformer oil nanofluids under thermal conditions to increase the age life-time of transformer oil.